Oncological and functional outcomes of elderly men treated with HIFU vs. minimally invasive radical prostatectomy: A propensity score analysis. Issue 1 (January 2018) - Capogrosso, Paolo; Barret, Eric; Sanchez-Salas, Rafael; Nunes-Silva, Igor; Rozet, François; Galiano, Marc; Ventimiglia, Eugenio; Briganti, Alberto; Salonia, Andrea; Montorsi, Francesco; Cathelineau, Xavier
Abstract: Aim: To assess outcomes of whole gland high-intensity focused ultrasound (HIFU) as compared with minimally-invasive radical prostatectomy (MIRP) in elderly patients. Materials & methods: Patients aged ≥70 years with, cT1-cT2 disease, biopsy Gleason score (GS) 3 + 3 or 3 + 4 and preoperative PSA ≤10 ng/mL were submitted to either whole-gland HIFU or MIRP. Propensity-score matching analysis was performed to ensure the baseline equivalence of groups. Follow-up visits were routinely performed assessing PSA and urinary function according to the International Continence Score (ICS) and the International Prostatic Symptoms Score (IPSS) questionnaires. Estimated rates of salvage-treatment free survival (SFS) overall-survival (OS), cancer-specific survival (CSS) and metastasis-free survival (MTS) were assessed and compared. Results: Overall, 84 (33.3%) and 168 (66.7%) patients were treated with HIFU and MIRP, respectively. MIRP was associated with a 5-yrs SFS of 93.4% compared to 74.8% for HIFU (p < 0.01). The two groups did not differ in terms of OS and MTS. No cancer-related deaths were registered. Patients treated with HIFU showed better short-term (6-mos) continence outcomes [mean-ICS: 1.7 vs. 4.8; p = 0.005] but higher IPSS mean scores at 12-mos assessment. A comparable rate of patients experiencing post-treatment Clavien-Dindo grade ≥III complications was observed within the two groups. Conclusions: Whole-gland HIFU is a feasible treatment in elderly men with low-to intermediate-risk PCa and could be considered for patients either unfit for surgery, or willing a non-invasive treatment with a low morbidity burden, although a non-negligible risk of requiring subsequent treatment for recurrence should be expected.